Surface water potential in Buriram province - Ritthirong Jaiyasin; Prida Thimakorn; Gupta, Ashim Das; Kumar, Devendra; Carl Duisberg-Gesell Schaft Cologne (Bangkok : Asian Institute of Technology, 1983)
Consequently, Buri Ram Province has the major problem in lack of water during dry season. Knowledge about t he surface water potential is necessary for management of water resource system. For such reasons and because of the requirement of water is increasing , this study is performed to investigate the surface water potential by rainfall - runoff model. The multiple linear regression analysis was used t o analyze t his model. Three river basins which cover area of Buri Ram Province were selected as the study area . Results from this investigation indicate t hat the model gives satisfactory prediction of current streamflow It was found t hat the sub- river basin possesses similar hydrological characteristics to that of basin of the main river.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1983
Keywords: Water resources development -- Thailand -- Buriram